Investigation of Q-Switched and Mode-Locked Pulses From a Yb3+-Doped Germano-Zirconia Silica Glass Based Fiber Laser - Wei-Cheng Chang; Yu-Sheng Lin; Yin-Wen Lee; Chien-Hsing Chen; Ja-Hon Lin; Pinninty Harshavardhan Reddy; Shyamal Das; Anirban Dhar; Mukul Chandra Paul (IEEE Photonics Journal)
The Q-switched and mode-locked (QML) pulses of an all normal dispersion Yb3+-doped fiber laser (YDFL) using the nonlinear polarization rotation technique with symmetric and asymmetric Q-switched envelopes were investigated. For QML pulses with a symmetric shape, the width of envelope decreases as the pump power increases, achieving a shortest duration of ∼1.4 μs. An alternate QML state of the YDFL exhibited an asymmetric envelope with a broad spectrum bandwidth, and whose short duration mode-locked pulses could be used as a light source for the cascaded Raman scattering generation through the injection of these high intensity QML pulses into an amplifier, using Yb3+-doped germano-zirconia silica (YD-GZS) glass based fiber as the gain fiber. In addition, the generation of a relatively broad spectrum near the IR range and the observation of some emission bands in the visible and UV range have been demonstrated at high pump power.